Children Affected by War and Armed Conflict: Parental Protective Factors and Resistance to Mental Health Symptoms - Slone, Michelle; Shoshani, Anat (Frontiers in Psychology, 2017)
Abstract This study investigated the role of parenting styles and parental warmth in moderating relations between exposure to political life events and mental health symptoms among 277 adolescents aged 12-14 and their parents living in southern Israel, who had been exposed to protracted periods of war, terrorism and political conflict. Adolescents completed the Political Life Events (PLE) scale, Brief Symptom Inventory and questionnaires regarding parenting style and parental warmth. The primary caregiver completed the Child Behavior Checklist for assessment of the child's internalizing and externalizing symptoms. Results confirmed that severity of PLE exposure was positively correlated with psychological distress and with internalizing and externalizing symptoms. Maternal authoritativeness and warmth functioned as protective factors and had moderating effects on the relation between PLE exposure and mental health symptoms. In contrast, maternal authoritarianism exacerbated the relation between PLE exposure and children's externalizing symptoms. Fathers' parenting style and warmth had no significant relationship with children’s mental health outcomes. These findings have important clinical and practical implications for parental guidance and support during periods of war and armed conflict.